Sustainability of technological dimension in dairy agribusiness. (November 2019) - Mastuti, R; Alham, F; Gustiana, C; Hanisah, H; Jamil, M; Muslimah, M; Rozalina, R
Abstract: This study aims to analyze sustainability index and status of technological dimension in dairy agribusiness in Batu City. Research methods applied were analysis Multidimensional Scaling (MDS) analysis, termed Rapuse, and Descriptive analysis. Study result was expressed in sustainability index and status. Moreover, to examine attributes sensitively affected sustainability index and status also the effect of error, analysis of Leverage and Monte Carlo was performed, followed with descriptive analysis. Data were obtained from key respondent and field observation. Four villages from three sub-districts in Batu City were purposively selected as research site, namely Village of Pesanggrahan, Tlekung, Oro-oro Ombo and Gunungsari. Sustainability analysis resulted in technological dimension of 60.40 or moderately sustainable condition and three leverage factors of AI breeding, adlibitum water application, and chopper use. Other factors in technological dimension should be taken care immediately since they sensitively have an effect on the increasing sustainability index and status with small error at confidence level of 95%. Factors included biogas installation, provision of dry concentrate, fresh milk handling, and cage cleanliness should be improved to increase sustainability index of technological dimension through role and support improvement of stakeholder consisted of milk cooperation, IPS, government institution related, and cattle farmers.